RESIDENCE PERMIT, JUDICIAL DISCRETION AND THE GEORGIAN CASE LAW - Gegenava, Dimitry; Tsiklauri, Salome (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
The legal framework governing residence permits represents a complex and multifaceted issue that intersects not only with international and domestic law but also with broader questions in the social sciences. In Georgia, this complexity is reflected in legal procedures through which the state authorizes individuals to reside within its territory. A distinctive feature of the process is the involvement of national security agencies, whose assessments are classified and accessible only to the judiciary. As a result, administrative judges are required to take proactive steps to request and evaluate confidential conclusions issued by the Counterintelligence Department. Even where procedural safeguards and appeal mechanisms are formally in place, the adjudication of residence permit disputes ultimately depends on the exercise of wide judicial discretion, which raises significant legal and institutional concerns. This article explores the specific role of classified opinions issued by the State Security Service of Georgia in the residence permit decision-making process. It analyzes the legal mechanisms for requesting and reviewing such information, the normative basis and limits of judicial discretion, and practical trends across all three instances of Georgia’s common court system.